2018
DOI: 10.1109/jbhi.2017.2688473
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Detection via Accelerometer and Gyroscope of a Smartphone

Abstract: We present a smartphone-only solution for the detection of atrial fibrillation (AFib), which utilizes the built-in accelerometer and gyroscope sensors [inertial measurement unit, (IMU)] in the detection. Depending on the patient's situation, it is possible to use the developed smartphone application either regularly or occasionally for making a measurement of the subject. The smartphone is placed on the chest of the patient who is adviced to lay down and perform a noninvasive recording, while no external senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
118
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 29 publications
0
118
1
1
Order By: Relevance
“…The patient is advised to lie down in a supine position, and the smartphone is placed on the patient’s chest to detect atrial fibrillation by measuring the regularity of cardiac mechanical activity. The device was reported to have a sensitivity of 94% and a specificity of 100% for detection of atrial fibrillation compared with simultaneous electrocardiography in this study 121. A larger case-control study, which included 150 consecutive patients in atrial fibrillation and 150 age and sex matched patients in sinus rhythm, reported the sensitivity and specificity of this device for detection of atrial fibrillation to be 95% (95% confidence interval 91% to 98%) and 96% (92% to 99%), respectively, compared with simultaneous five lead telemetry electrocardiographic recording interpreted by two cardiologists 122…”
Section: Emerging Technologiesmentioning
confidence: 69%
“…The patient is advised to lie down in a supine position, and the smartphone is placed on the patient’s chest to detect atrial fibrillation by measuring the regularity of cardiac mechanical activity. The device was reported to have a sensitivity of 94% and a specificity of 100% for detection of atrial fibrillation compared with simultaneous electrocardiography in this study 121. A larger case-control study, which included 150 consecutive patients in atrial fibrillation and 150 age and sex matched patients in sinus rhythm, reported the sensitivity and specificity of this device for detection of atrial fibrillation to be 95% (95% confidence interval 91% to 98%) and 96% (92% to 99%), respectively, compared with simultaneous five lead telemetry electrocardiographic recording interpreted by two cardiologists 122…”
Section: Emerging Technologiesmentioning
confidence: 69%
“…Simple time domain [47,61,81,82,107] Statistical time domain [41,56,65,106] Simple frequency domain [41,56] Statistical frequency domain [40,41,47,78] 2.4. Machine Learning…”
Section: Scg Features Referencementioning
confidence: 99%
“…For each ROI, we record the mean RGB values of pixels inside it and further eliminate the noises by a moving-average filter on the nearest 15 points. Then, we employ three various (6,7,11,12) pulse extraction methods [12]- [14] to acquire the videoextracted pulse rhythms. An ideal example of the final pulse rhythm signals can be seen in Fig.…”
Section: A Roi Detection and Pulse Signal Extractionmentioning
confidence: 99%
“…However, the acquisition of ECG signals requires specific biomedical equipment, which limits the application of monitoring AF risk in daily life. Recently, many researchers [9]- [11] have tried to capture the cardiac pulse signal with the wearable device and smart phone for predicting AF. Nevertheless, the measurement needs to be conducted in a skin-contact manner that is inconvenience and uncomfortable for the examinee.…”
mentioning
confidence: 99%